Artificial Intelligence: : new subject of law? Biolegal implications and reflections on the role of this tool within the formation of legal relationships. - Santome-Sánchez, Aldo Alesandro (2024)
Today, we live in an era where the participation of Artificial Intelligence is already part of our daily lives. Its increasing use compels the legal framework to question the role of such technologies within the legal order. In this context, there is doctrinal uncertainty about whether, due to the autonomy with which it seems to operate, AI should be considered a new type of legal subject. This would imply that AI could exercise various types of subjective legal situations, becoming a decisive part of community life. Ultimately, it is concluded that, despite its novel functions, AI cannot be equated with the condition of a person, which is the foundation of the idea of a legal subject, due to its inability to have feelings or generate private judgments of autonomy, as well as its incapacity to assess its own behavior.